The contribution of social tourism to sustainable tourism: a case study of seasonally adjusted programmes in Spain - Cisneros-Martinez, José David; McCabe, Scott; Fernández- Morales, Antonio (Taylor & Francis, 2017)
Recent policy from the European Union has attempted to justify social tourism initiatives on the basis that they lead to a more sustainable tourism industry. However, the majority of latest research in the field has been focused on the benefits for participants, with the addition of some evidence on the economic impacts of such programmes on destinations, which have pointed towards sustainability outcomes including: a longer tourism season, more even spread of demand, and longer periods of employment for tourism workers. Yet there is a lack of direct evidence linking such programme to these outcomes. This paper aimed to explore this important disconnect between policy assumptions and evidence-based outcomes through an analysis of the deseasonalising effects of the Spanish social tourism programme for older people. The research found that this programme does have an effect on the seasonal nature of employment and economic activity in most regions studied, but that the huge volume of demand from international tourists in the high seasons masks the quantitative effects in the regions with the highest seasonal concentration of international tourists. Recommendations for policy and practice in sustainable tourism are made that are transferable to many countries and regions that adopt social tourism programmes.